Conveyancing - Sarton, Priscilla. author. aut Link
XX, 280 p.
Keywords: Part of Macmillan's series of law books, this text is intended for law undergraduates. It provides an introduction to conveyancing and the laws which apply to it. Other titles in the series include "Basic English Law", "Company Accounts", "Criminal Law" and "Personnel Administration".